DISCHARGE CHARACTERISTIC OFSILVER SOLID STATE BATTERY. - E. Kartini; Gunawan Gunawan; Mardiyanto Mardiyanto; A. Hindasyah; R. Salam (Jurnal Sains Materi Indonesia, 2006)
DISCHARGE CHARACTERISTIC OFSILVER SOLID STATE BATTERY. Asilver solid electrolyte based on superionic glass (AgI)x(AgPO3)1-x has been produced by melt-quenching method. The solid state batteries have been fabricated with the cell configuration: Anode//(AgI)x(AgPO3)1-x//Cathode. Ag-metal was used as an anode, and Iodine was used as a cathode. The solid state battery discharge characteristic has been carried out under two different load conditions, 20 kΩ and 50 kΩ. Cell parameters viz. current density, power density, discharge capacity and energy density were evaluated and reported. The power density of the solid state battery was approximately larger than 3.45 mWh.